Hegemoniczna męskość i dywidenda patriarchatu. O społecznej teorii płci kulturowej Raewyn Connell - Skoczylas, Łukasz (Refleksje. Pismo naukowe studentów i doktorantów WNPiD UAM, 2018)
The article gives a brief introduction to the social theory of gender relations created by R. Connell. It discusses mainly the concept of hegemonic masculinity, showing its main features and present form. The article also underlines Connell’s understanding of cultural gender. Moreover, masculinity in different cultures and the sources of modern masculinity patterns are presented.